Epidemiología molecular del Herpesvirus humano tipo 8 (HHV-8) en Argentina: asociación con eventos migratorios humanos - Hulaniuk Wolaniuk, María Laura (2020)
HHV-8 genetic diversity shows a worldwide distribution exhibiting a clear ethnic and geographic clustering. Data regarding the prevalence, genetic diversity and evolutionary history of HHV-8 is still scarce in multi-ethnic Latin American populations.\nThe prevalence of HHV-8 was determined in 772 blood donors, 101 HIV-1 infected subjects and 93 Kaposi?s Sarcoma patients. ORF-26 and ORF-K1 were analyzed for subtype assignment. A mini-sequencing protocol was designed to identify subtypes. Genetic ancestry was determined by ancestry-sensitive DNA markers from autosomal, Y and mitochondrial chromosomes. Phylogeographic analysis was performed in the ORF-K1.\nHHV-8 DNA was less prevalent among blood donors (p<0.0001), and, among those, viral prevalence was higher among donors from north-western Argentina than from the metropolitan area (p=0.001), Bolivians (p=0.0008), Peruvians and Paraguayans. Analyses of ORF-26 revealed that most strains were subtype A/C, followed by subtypes J, B2, K or R. ORF-K1 analyses revealed the presence of subtypes A, B, C and F. The mini-sequencing technique developed in this thesis was a fast, efficient and cheap to identify the most prevalent subtypes in Argentina. Subtypes A/C and J were significantly associated with Native (p=0.004) and non-Native American maternal haplogroups (p<0.0001), respectively. HHV-8 was introduced from Africa, Europe and Latin America.\nThese results reveal the prevalence and HHV-8 genetic diversity in Argentina and their relationship with human migrations.